Do EU structural funds promote regional growth?: New evidence from various panel data approaches - Mohl, Philipp; Hagen, Tobias (Regional science and urban economics, 2010)
This paper analyses the economic growth effects of EU structural funds extending the current literature by at least three aspects: Firstly, we make use of a new structural funds dataset of 126 NUTS-1/NUTS-2 regions as well as more precise measures of structural funds by distinguishing between Objective 1, 2, and 3 payments. In doing so, we include the Financial Perspective 2000-2006, which has not been analysed before. Secondly, we address the problem of endogeneity in a panel context by basing the identification on internal instruments via a system GMM estimator. Finally, we control for spatial spillover effects by applying a spatial panel econometric estimator. Our results show that Objective 1 payments in particular do, in fact, promote regional economic growth, whereas the total amount of Objectives 1, 2, and 3 do not have a positive and significant impact on the EU regions' growth rates.